Incidence of Sindbis Virus in Hospitalized Patients With Acute Fevers of Unknown Cause in South Africa, 2019–2020 - Meno, Kgothatso; Yah, Clarence; Mendes, Adriano; Venter, Marietjie (Frontiers in Microbiology, 2022)
Background: Sindbis virus (SINV) is a mosquito borne alphavirus that is widely distributed worldwide. Little is known about the febrile and neurological disease burden due to SINV in South Africa. Patients and methods: Clinical samples of patients with acute fevers of unknown cause (AFDUC) were collected through the African Network for Improved Diagnostics, Epidemiology and Management of Common Infectious Agents (ANDEMIA) at 3 sentinel hospital surveillance sites in South Africa. In total, 639 patients were screened using a PCR based macroarray that can simultaneously detect nucleic acids of 30 pathogens, including SINV from January 2019-December 2020. Serum samples were randomly selected from the arbovirus season (January-June) and also screened with a commercial indirect immunofluorescence assay for anti-SINV IgM. In addition, 31 paired CSF specimens from the same patients were screened for IgM. Micro-neutralization assays were performed on all IgM positive samples . Results: None of the specimens tested positive for SINV by molecular screening, however, 38/197 (19.0%) samples were positive for SINV specific IgM. A total of 25/38 (65.8%) IgM positive samples tested positive for SINV neutralizing antibodies, giving an overall incidence of 12.7%. Furthermore, 2/31 (6.5%) CSF specimens tested positive for IgM but were negative for neutralizing antibodies. There was a higher incidence of SINV positive cases in Mpumalanga (26.0%) than Gauteng province (15.0%). The most significant months for IgM positive cases were April 2019 (OR = 2.9, p <0.05), and May 2020 (OR= 7.7, p <0.05).